Criteria for Evaluation of Urban Green Spaces: A Case of Macedonian Cities - Penchikj, Divna; Hadzi pecova, Stefanka; Brndevska Stipanović, Viktorija (Ss. Cyril and Methodius University in Skopje Hans Em Faculty of Forest Sciences, Landscape Architecture and Environmental Engineering, 2022)
The constant growth of cities, their densification, the increase in the number of inhabitants, the problems with pollution of all kinds and the conditions caused by climate change, increase the pressure on the quality of life in urban areas. The commitment to achieving sustainable urban development is a globally accepted concept, but its implementation, in many respects, is a major challenge. Most often, the quality of life in cities is measured or evaluated through developed sets of criteria and indicators, the establishment of which is expected to be easier assessment and comparability at local and global level. Macedonia has long been in the "race" for sustainable and green cities, but in determining the policies for providing, planning, financing, construction and maintenance of urban green spaces, there is a lack of applicable set of criteria and indicators for their evaluation. Hence, this paper aims to examine the conditions for establishing operational criteria for the assessment of public urban green spaces in our country, regarding to economic, social and environmental issues. The research was conducted through review and analysis of: theoretical basis, legislation, experiences from other cities and local characteristics. The results of the paper would provide guidance for establishing a set of criteria and indicators that would help all stakeholders involved in the process of creating sustainable cities and specifically urban green spaces, to improve the quality of life in Macedonian cities.
Keywords: quality of life; urban life; urban green spaces; sustainable cities; criteria; indicators